On Fixed Points of α-ψ-Contractive Multivalued Mappings in Cone Metric Spaces - Marwan Amin Kutbi; Jamshaid Ahmad; Akbar Azam (Abstract and Applied Analysis)
We define the notion of α*-ψ-contractive mappings for cone metric space and obtain fixed points of multivalued mappings in connection with Hausdorff distance function for closed bounded subsets of cone metric spaces. We obtain some recent results of the literature as corollaries of our main theorem. Moreover, a nontrivial example of α*-ψ-contractive mapping satisfying all conditions of our main result has been constructed.